IMPROVING THE CAPACITY AND OPERATIONAL EFFICIENCY OF AN ON-STREET PARKING SYSTEM USING DATA-BASED PARKING MANAGEMENT STRATEGIES: CASE STUDY OF WATT MARKET IN CALABAR, SOUTH-SOUTH NIGERIA (Nigerian Journal of Technology, 2020)
Solving parking challenges in a manner that is sustainable would require a shift from using up more scarce land resources in providing supply to meet an unending demand for parking. Parking management is the approach of tackling parking challenges that efficiently utilizes scarce resources to meet demand in a sustainable way. This paper studied an on-street parking system in the central business district with the aim of proffering policies and strategies that can help improve the capacity and operational efficiency of the park. Parking inventory and the license plate method were employed in analyzing the parking characteristics of the park. By introducing a parking duration restriction, more capacity could be accommodated on the current available lots. A 90-minute limit would accommodate at least 106 more vehicles and increase the turnover from 13 to 14 vehicles per lot for the duration of survey, thus improving operational capacity and efficiency. The paper shows that parking management strategies that are effective in making the difference should be employed based on adequate field surveys, observations and analysis. http://dx.doi.org/10.4314/njt.v39i2.4